Prognosis of Stage IV Gastric Cancer Patients - Kim, Ho Gu; Kang, Dong Yeon; Lee, Jae Hyuk; Kim, Dong Yi (Lietuvos chirurgija, 2022)
Aim. This study evaluated the survival of gastric cancer patients with metastasis to the hepatoduodenal, retropancreatic, mesenteric, and para-aortic lymph nodes. Materials and methods. We analyzed the survival rate of 435 gastric cancer patients who underwent operation from 2001 to 2010 at the Department of Surgery, Chonnam National University Hospital. There were 43, 25, 16, and 55 patients with metastasis to the hepatoduodenal, retropancreatic, mesenteric, and para-aortic nodes, respectively. Results. Based on tumor location, metastasis to the para-aortic lymph nodes was more common in upper-third cancer, and that to the hepatoduodenal lymph nodes was more common in lower-third cancer. The survival rate of patients with non-regional lymph node metastasis was better than that of patients with hepatic metastasis or peritoneal dissemination (p < 0.05). Conclusion. We recommend performing a more extended lymphadenectomy than a D2 lymphadenectomy in patients with advanced gastric cancer those having metastasis to the hepatoduodenal nodes.